Evaluation of oxygen transfer of diffused aeration for high density fish culture under recirculating aquaculture system (RAS) - Nur Farizah Jabarullah (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
This study was carried out to study the effects of air flow rate, salinity and diffuser pore size on dissolve oxygen. The effect were examined in this experiment were: the effect of diffusers pore diameter (1 mm and 3 mm) the effect of air flow rate (4 L/min and 8 L/min) and the effect of salinity ( 0.25 ppt and 35 ppt). This experiment resulted in 11 combinations of diffusers pore size, air flow rate and salinity. KLa values were derived by fitting the mass transfer equation to the data of dissolved oxygen (DO) versus time. Three factors that affect the KLa value were studied. Optimizing the experiment were done by using Design Expert software and ANOVA analysis was ran in order to determine the significance of factors that affect KLa value. Based on ANOVA, air flow rate and salinity rate were significantly affected KLa and oxygen transfer efficiency. The highest oxygen transfer rate achieved was 0.0056 mg/L. Through this optimal design, it provided a solution of air flow rate (11.9999 L/min, salinity (0.25 ppt), sparger s hole size 1mm, which it manage to get 0.005598 mg/L of oxygen transfer rate.